A multimodal analysis of Bangladeshi fairness product advertisements / Shushmita Hossain Khan - Shushmita , Hossain Khan (2020)
The notion of beauty is associated with fair skin tone in Bangladesh. Bangladeshis have varied skin tones although generally most of the people have a dark complexion. Fairness product advertisements tend to suggest that fair complexion is essential for marriage, successful career and promote that using their products can help women to achieve the perfect face, partner, and expected behavior from the society as well as acceptance from the opposite sex. This indicates that fair skin means superiority and beauty in Bangladeshi context. Although these advertisements have gone through some changes in last five years, within these, the advertisements still seem to influence women with similar messages using but different strategies. The study aims to highlight the use of multimodal resources in Fair & Lovely fairness-product advertisements and techniques applied by the advertisers to influence their customers. Kress and Van Leeuwen’s framework of multimodal analysis (1996) along with Machin (2016) and Ledin and Machin (2018) are utilized as analytical tools. To investigate this issue, this study undertakes the analyses of two data sources: 10 television advertisements (multimodal analysis) and triangulated with 35 responses through an online survey (thematic analysis). Findings suggest that the advertisers use various discursive techniques to influence women to reconstruct their ideology of “fairness” and “beauty” through visual and verbal aspects of the advertisements.